Regulation of Carbon Partitioning in the Seed of the Model Legume Medicago truncatula and Medicago orbicularis: A Comparative Approach - Song, Youhong; He, Liang; Wang, Xin-Ding; Smith, Nathan; Wheeler, Simon; Garg, Manohar L.; Rose, Ray J. (Frontiers in Plant Science, 2017)
The proportion of starch, protein and oil in legume seeds is species dependent. The model legume, Medicago truncatula, has predominantly oil and protein stores. To investigate the regulation of seed oil production we compared M. truncatula with Medicago orbicularis, which has less oil and protein. The types of protein and fatty acids are similar between the two species. Electron microscopy indicated that the size and distribution of the oil bodies in M. orbicularis, is consistent with reduced oil production. M. orbicularis has more extruded endosperm mucilage compared to M. truncatula. The cotyledons have a greater cell wall content, visualized as thicker cell walls. The reduced oil content in M. orbicularis is associated with increased expression of the MtGLABRA2-like (MtGL2) transcription factor, linked to an inverse relationship between mucilage and oil content in Arabidopsis. The expression of the pectin biosynthesis GALACTURONOSYLTRANSFERASE (GAUT) genes, is also increased in M. orbicularis. These increases in extruded mucilage and cell wall storage components in M. orbicularis are accompanied by reduced expression of transcriptional regulators of oil biosynthesis, MtLEAFY COTYLEDON1-LIKE (MtL1L), MtABSCISIC ACID-INSENSITIVE3 (MtABI3) and MtWRINKLED-like (MtWRI), in M. orbicularis. The reduced oil in M. orbicularis, is consistent with increased synthesis of cell wall polysaccharides and decreased expression of master transcription factors regulating oil biosynthesis and embryo maturation. Comparative investigations between these two Medicago species is a useful system to investigate the regulation of oil content and carbon partitioning in legumes.